The Problems Experienced By Black Stroke Patients in Soweto, South Africa - L. A. Hale; C. J. Eales; A. Steward; V. U. Fritz (AOSIS, 1999)
A purposeful sample of Black Sowetan residents who had sustained a stroke were studied to identify the problems they were encountering after discharge back to their homes. A descriptive qualitative approach was used comprising semi-structured interviews in the subjects' homes. Audio recorded data was transcribed in extenso, and coded into themes. The data revealed that the subjects' lacked knowledge of their disease processes. However, medication non-complianc was largely due to financial and transportation difficulties in attending clinics. Although most of the sample was able to walk, they felt the need for improved walking ability, as they were scared of falling. Most were independent in ADL, yet they, and their families perceived them to be otherwise, leaving the subjects with a sense of worthlessness. Pain in the shoulder and stiffness were the common secondary problems encountered. There is a need to educate stroke victims with regards to their disease, it's secondary complications and their capabilities following stroke. Safe walking must be ensured before discharge.